(untitled) (Jurnal Bahasa, 2023)
The grammatical function of objects often causes confusion among Malay language users even though explanations have been given in the reference grammar book, Tatabahasa Dewan. Based on the issue of object confusion, this study aims to provide a theoretical description of the grammatical function of objects in Malay sentences by examining the syntactic behaviour of four verbs, namely ’mencari’, ’mencarikan’, ’menderma’, and ’mendermakan’. The theoretical explanation is based on the Minimalist Program. From a methodological aspect, this study uses data from the DBP corpus and the Dibuat Individu dengan Yakin (DIY) corpus from the newspaper Berita Harian Online. In addition, a questionnaire survey was also conducted to assess the acceptability of sentences based on the intuition of native Malay speakers. The results of the study show that native Malay speakers accept that the sentences with ’mencari’ and ’menderma’ have two arguments that function as the subject and the direct object. For the verb ’mencarikan’, it was found that native Malay speakers tend to construct two objects structure represented by a noun phrase. However, the findings of this study show that for the verb ’mendermakan’, the subjects of this study tend to choose the dative construction, which is FN + verb + FN + FP. This study is of the opinion that the indirect object in the Malay language is given a choice of whether it consists of the construction FN + FN or FN + FP. This dative construction is in line with the native speaker’s intuition and theoretical justification. Keywords: Transitive verb, dative, indirect object, Minimalist Program, Malay language, preposition phrase Full text: PDF